Suicidal Behaviors and Associated Factors Among Adult Psychiatric Patients Attending Psychiatric Clinic at Public Hospitals in Ethiopia: A Cross-Sectional Study - Jerman Dereje MSc; Dawit Firdisa MPH; Aklilu Tamire MPH; Seid Tesi MSc; Mesay Dechasa MSc; Tilahun Abdeta MSc (SAGE Publishing, 2024)
Suicidal behaviors in persons with mental illnesses are the most prevalent psychiatric crises, requiring scholars and mental health task teams to prioritize public health concerns. However, there is a scarcity of data in Ethiopia, particularly for patients with mental illness. As a result, the goal of this study was to assess the prevalence of suicidal behaviors and associated factors among individuals with mental illness visiting public hospital psychiatric clinic units in eastern Ethiopia. A facility-based cross-sectional study was conducted from October 15 to November 15, 2022, with 411 individuals with mental illness visiting psychiatric clinic units at public hospitals in eastern Ethiopia. To select participants in the study, a systematic random sampling method was used. A structured face-to-face interview was used to gather data. The Suicidal Behavior Questionnaire-Revised (SBQ-R) was used to measure suicidal behaviors. Epidata 3.1 version was used to enter the data, and SPSS version 24 was used to analyze it. Both bivariable and multivariable logistic regression analyses were employed. In the final model, variables with p-values less than 0.05 were considered statistically significant. To identify variables associated with suicidal behavior, the adjusted odds ratio (AOR) and 95% confidence interval (CI) were utilized. Out of a total of 411 eligible participants, 402 involved in this study, giving a response rate of 97.8%. The prevalence of suicidal behavior was 46.3%, (95% CI: 41-50.7). Depression (AOR = 2.21,95% CI: 1.04, 4.69), medication non-adherence (AOR = 1.95, 95% CI: 1.19, 3.18), bipolar disorders (AOR = 1.79, 95% CI: 1.55, 3.53), and current alcohol use (AOR = 1.81, 95% CI: 1.01, 3.28) were variables associated with suicidal behaviors. This study found a high rate of suicidal behaviors among adult individuals with mental illness in public hospitals in eastern Ethiopia. Suicidal behavior was highly associated with depression, bipolar disorders, current alcohol use, and medication non-adherence. Psychiatric professionals should assess patient suicidal risk assessment routinely and should put the diagnosis with suicidal if the client is suicidal so that every professional focuses on treatment besides the medication. Special attention is required for individuals who present associated features, such as history of medication non adherence, depression, and overall bipolar disorders.